Eco-morphological traits of leaf of the Campanula L. species (CHORNOMORSKI BOTANICAL JOURNAL, 2015)
The functional features of leaf ecophysiology and ecomorphology of native and introduced of Campanula species in culture in the Ukraine steppe for the detection of their adaptive traits were studied. The study was performed with the use of modern methods, comparison parameters of leaf species groups conducted using test ANOVA. The influence of climatic factors of natural habitat of species on the functional ecomorphology of leaf and successful their introduction was revealed. Species of Campanula from warmer habitats are characterized greater the leaf width of both formations and the petiole length of rosette leaf. Species differ more in weight of rosette leaves from more humid regions, cauline leaf – from warmer regions with high evaporation. It was found that species from drier warmer regions with high evaporation of rainfall have low specific leaf area (SLA) and high values of m1/m of cauline leaf. The successful introduction of Campanula species in the Ukraine steppe increased in plants from arid habitats with high variation of evaporation, difference of precipitation and evaporation, duration of the period with temperatures above 10°C. Thus confirming the importance of eco-biological features of species in their adaptation to new environmental conditions. Compared with resistant species (group V) petrophytes of midland and subalpine zones (II), species of forests and meadows (III) and forests species (IV) have a smaller petiole diameter rosette leaves (dp), hence smaller hydraulic conductivity of leaf petiole, but in the conditions of introduction petrophytes accumulate despite this, more water through transpiration regulation, forest species – less. Petrophytes of midland and subalpine zones and species of forests and meadows are more specific leaf area (SLA) of cauline leaf, forests species – higher SLA of different formations. Species of these groups are adapted to arid conditions due to the high photosynthetic energy use efficiency (PEUE), water use efficiency (WUE) as their low. Species of forests and meadows compared with alpine and forest species accumulate large amounts of water in the rosette leaves, however, compared with the first to have lower efficiency of its use, as compared to the second more. Alpine species compared with petrophytes of midland and subalpine zones and species of forests and meadows characterized by high the maximum photosynthesis (Amax) and photosynthetic energy use efficiency (PEUE) cauline leaves; compared with the first have a greater hydraulic conductivity of leaf petiole and adapted to the new conditions of changes in epidermalstomatal complex of rosette leaves, which increases water use efficiency (WUE) in the spring.
Keywords: adaptive traits, leaf, eco-morphological features, species of Campanula, climatic factors.